Prospecting the state of the art of scientific research on technology readiness level (Research, Society and Development, 2023)
The purpose of this is to research the state of the art of the Technology Readiness Level - TRL theme, which is a methodology for measuring the level of technological maturity for innovation projects. A bibliometric study was carried out on the subject in the Scopus research base in the last five years. As a result, it was identified that the state of the art of the TRL theme is still scarce in terms of discussions about its importance within the context of innovation ecosystems worldwide. In the analyses, it was possible to identify the main authors and journals that publish on the subject, as well as the main keywords and the most referenced sources in the selected articles. In an analysis of the findings of 4 of the main articles, it was noticed that the TRL has great relevance in the works undertaken, and that it is used in conjunction or even adapted to a given reality. The scarcity of articles dealing with TRL was a limitation found.